Analisis Pemahaman Masyarakat Mengenai Mekanisme Pembiayaan Bank Syariah di PT Bank SUMUT Syariah CAPEM HM YAMIN - Rahmi Syahfitri Harahap; Atika Atika (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
In terms of progress and development, Islamic banking which implements a profit-sharing system runs side by side with conventional banking which applies an interest system. The problem that occurs in Islamic banks is the low public understanding of Islamic banking, especially caused by the large number of conventional banks so that Islamic banking is still underestimated. The purpose of this study is to find out how people's understanding of Islamic banking at PT. Bank Sumut Syariah Capem HM Yamin. From the research results by conducting interviews with 11 customers of PT. Bank Sumut Syariah Capem HM Yamin which has been carried out by the author, as many as 7 customers have understood the mechanism of Islamic bank financing and 4 customers have not understood the mechanism of Islamic bank financing, it can be concluded that public understanding of Islamic bank financing at Bank Sumut Capem HM Yamin has started to expand. Even so, it is still necessary to expand the information obtained by the public from Islamic banks, both through socialization and education, as well as through media such as television, print media and social media so that people's understanding of Islamic bank financing can be comprehensive.